Upaya Meningkatkan Kelincahan Pada Olahraga Tradisional Gobak Sodor Melalui Latihan Essential Agility Drills - Dicky Reva Apriana Sanga Dwi; Citra Resita; Wahyu Erfandy; Moch Asmawi; Heni Widyaningsih (JUARA : Jurnal Olahraga, 2022)
The purpose of this study was to examine the effects or benefits of increasing agility in the traditional sport of Gobak Sodor with the Essential Agility Drills method on STKIP Muhammadiyah Kuningan students. This study used a True Experiment Design with the division of the experimental group being given treatment and the control group not being given any treatment. This study used a sample involving 60 students (30 experiments, 30 controls). The sampling technique used was purposive sampling. The test instrument used to measure agility was the zig-zag run test as a pretest and posttest for the two groups to know the differences in their agility. The t-test analysis showed a Sig value of 0.00 <0.05, meaning that there was a significant difference in the two groups, but the experimental group was superior to the control group with a percentage increase of 9.76%, while the control group had a smaller percentage than the experimental group, namely 1 0.02% means 9.76%> 1.02%, which means that the experimental group has a higher rate of increase compared to the control group, meaning that the Essential Agility Drill training method is very influential on agility in the traditional sport of Gobak Sodor.